Social-ecological systems approach in drought-food insecurity nexus research - Debashis Roy; Yollanda Chepkoech Korir; Steven A. Gillespie; Md Sarwar Hossain (npj Sustainable Agriculture)
Abstract Drought is increasingly seen as the next “pandemic,” threatening global populations and progress towards achieving zero hunger by 2030. Although drought and food security are well-researched, no studies synthesize the progress and gaps in drought-food insecurity research using the social-ecological systems (SES) approach. Through a systematic review of 186 peer-reviewed studies in Asia and Africa, sourced from Web of Science and Scopus, we identified knowledge gaps and application of an SES approach in the drought-food insecurity nexus. Most studies focused on either social or ecological perspectives; applied quantitative approaches; did not specify drought types; emphasized food availability and access; and did not assess adaptation strategies. The key gap identified was the limited application of a holistic SES approach for achieving the zero-hunger goal. Unlike traditional approaches, our proposed conceptual framework offers a holistic lens for investigating SES components and their complex relationships, and new inquiries in the drought-food insecurity nexus.